2015
DOI: 10.1088/0004-6256/149/4/130
|View full text |Cite
|
Sign up to set email alerts
|

Csi 2264: Characterizing Young Stars in NGC 2264 With Short-Duration Periodic Flux Dips in Their Light Curves

Abstract: We identify nine young stellar objects (YSOs) in the NGC 2264 star-forming region with optical CoRoT light curves exhibiting short-duration, shallow periodic flux dips. All of these stars have infrared excesses that are consistent with their having inner disk walls near the Keplerian co-rotation radius. The repeating photometric dips have FWHMs generally less than 1 day, depths almost always less than 15%, and periods (3 < P < 11 days) consistent with dust near the Keplerian co-rotation period. The flux dips v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 69 publications
11
76
0
Order By: Relevance
“…There is some similarity between the light curves of some of the stars in Table 1 and some of the stars identified in recent years as "dippers" in Orion, NGC2264, and Upper Sco (Morales-Calderon et al 2011;Cody et al 2014;Stauffer et al 2015;Ansdell et al 2016); these stars are also sometimes referred to as AA Tau analogs (Bouvier et al 1999;Alencar et al 2010;McGinnis et al 2015). The light curves of AA Tau stars show a wide diversity, with most of them showing very broad and structured flux dips that are quite dissimilar from our Upper Sco stars and thus do not serve as plausible comparison objects.…”
Section: Could Variable Extinction From a Primordial Disk Explainmentioning
confidence: 56%
“…There is some similarity between the light curves of some of the stars in Table 1 and some of the stars identified in recent years as "dippers" in Orion, NGC2264, and Upper Sco (Morales-Calderon et al 2011;Cody et al 2014;Stauffer et al 2015;Ansdell et al 2016); these stars are also sometimes referred to as AA Tau analogs (Bouvier et al 1999;Alencar et al 2010;McGinnis et al 2015). The light curves of AA Tau stars show a wide diversity, with most of them showing very broad and structured flux dips that are quite dissimilar from our Upper Sco stars and thus do not serve as plausible comparison objects.…”
Section: Could Variable Extinction From a Primordial Disk Explainmentioning
confidence: 56%
“…In some cases where the stellar rotation is evident, such as the case of Mon 21, the dimming events have been observed to be synchronized with the stellar rotation period (Stauffer et al 2015). The coincidence between stellar rotation and the orbital period of transiting debris in this model is a natural consequence of disk-locking, where the inner disk edge is truncated near the corotation radius due to interactions with the stellar magnetosphere.…”
Section: Obscuration By a Circumstellar Disk?mentioning
confidence: 75%
“…The advent of highcadenceprecision photometry using space telescopes has revealed an unprecedented level of detail to this general class of variable young stars now called "dippers" (Cody et al 2014;Stauffer et al 2015;Ansdell et al 2016).…”
Section: Obscuration By a Circumstellar Disk?mentioning
confidence: 99%
“…differs from that of Alencar et al (2010), since we were able here to use the simultaneous FLAMES spectroscopy to refine our classification. In addition, Stauffer et al (2015) identified a new subclass of stars with variable extinction light curves that show periodic, shallow, and short-duration flux dips that are approximately Gaussian in shape. There is some overlap between this new class and the classical AA Tau systems, since a few AA Tau-like stars also present narrow dips superposed on the broad deep minima, as explained in their paper.…”
Section: Morphology Of the Corot Light Curvesmentioning
confidence: 99%